PENINGKATAN KESADARAN MASYARAKAT TERHADAP KEBERSIHAN DAN MENGEMBANGKAN UMKM DI KELURAHAN BAKALANKRAJAN - Achyunda Putra, Firnanda Al-Islama Achyunda Putra; Arief, Rizza Muhammad; Arifin, Yulia Natasya Farah Diba (LPPM Universitas Al Muslim, 2024)
Improving cleanliness is one way to optimize public health. This community service activity has the theme of cleanliness and development of MSMEs, which is carried out by KKN students in Bakalankrajan Village. Students helped develop 2 MSME products and held a